2010
DOI: 10.2147/opth.s13101
|View full text |Cite
|
Sign up to set email alerts
|

Progression rate of total, and upper and lower visual field defects in open-angle glaucoma patients

Abstract: PurposeWe evaluated the progression rate of total, and upper and lower visual field defects in treated open-angle glaucoma patients.Patients and methodsThis study was a retrospective, nonrandomized, comparative study. Five-hundred forty-four eyes from 315 Japanese open-angle glaucoma patients were examined. The mean deviation (MD) and total deviation (TD) for both the upper and lower slopes on the Humphrey Field Analyzer were calculated and compared in high-tension glaucoma (>21 mmHg) and normal-tension glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…While the rate of VF loss in POAG eyes, [41][42][43][44][45][46][47][48][49][50][51][52] as well as differences between the patterns of VF loss in POAG and PACG eyes, 27,30,34,53 has been reported previously, this is, to our knowledge, the first study directly investigating the differences in the rate of VF loss as well as the superior-inferior asymmetry between POAG and PACG eyes with automated perimetry. Lee and colleauges compared the rate of VF loss using the Goldmann perimetry; however, their relatively small number of eyes (25 POAG eyes and 23 PACG eyes) makes the comparison challenging.…”
Section: Discussionmentioning
confidence: 48%
“…While the rate of VF loss in POAG eyes, [41][42][43][44][45][46][47][48][49][50][51][52] as well as differences between the patterns of VF loss in POAG and PACG eyes, 27,30,34,53 has been reported previously, this is, to our knowledge, the first study directly investigating the differences in the rate of VF loss as well as the superior-inferior asymmetry between POAG and PACG eyes with automated perimetry. Lee and colleauges compared the rate of VF loss using the Goldmann perimetry; however, their relatively small number of eyes (25 POAG eyes and 23 PACG eyes) makes the comparison challenging.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies have shown that VF progression occurs more rapidly in the superior hemifield than the inferior hemifield in OAG. 16,17,21,22 Cho and Kee 17 recently reported that the VF progression rate of the superior central 108 (À0.911 dB/y) in NTG eyes with initial superior hemifield defects differed significantly from the VF progression rate of the inferior central 108 (À0.16 dB/y) in NTG eyes with initial inferior hemifield defects. Although it is difficult to compare studies owing to variations in the study populations and the research design, our results are in line with those of Cho and Kee 17 in that the superior 108 zone in the HMF group (À1.28 dB/y) showed more rapid VF progression than the inferior 108 zone (À0.75 dB/y, P < 0.0125).…”
Section: Discussionmentioning
confidence: 98%
“…6,7 On the basis of both previous investigations and our study results, visual field deterioration in high-tension glaucoma is related to IOP and its highest levels. 10,36 Previous investigations reported that the IOP could be effectively reduced by glaucoma surgery. In addition, establishing target pressures may help manage high-tension glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%